2013
DOI: 10.1007/s00253-013-4887-9
|View full text |Cite|
|
Sign up to set email alerts
|

Bacterial lipoxygenases, a new subfamily of enzymes? A phylogenetic approach

Abstract: Lipoxygenases (EC. 1.13.11.12) are a non-heme iron enzymes consisting of one polypeptide chain folded into two domains, the N-terminal domain and the catalytic moiety β-barrel domain. They catalyze the dioxygenation of 1Z,4Z-pentadiene moieties of polyunsaturated fatty acids obtaining hydroperoxy fatty acids. For years, the presence of lipoxygenases was considered a eukaryotic feature, present in mammals, plants, small marine invertebrates, and fungi, but now, some lipoxygenase sequences have been detected on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 36 publications
3
60
0
Order By: Relevance
“…Mycelia of M. oryzae metabolize linoleic acid sequentially to 8R-hydroperoxy-and 7S,8S-dihydroxylinoleic acids by linoleate 7,8-diol synthase (7,. Gene deletion of 7,8-LDS does not impair rice infection (12).…”
Section: Introductionmentioning
confidence: 99%
“…Mycelia of M. oryzae metabolize linoleic acid sequentially to 8R-hydroperoxy-and 7S,8S-dihydroxylinoleic acids by linoleate 7,8-diol synthase (7,. Gene deletion of 7,8-LDS does not impair rice infection (12).…”
Section: Introductionmentioning
confidence: 99%
“…LOX-isoforms occur in bacteria [24] but they are not widely distributed [5]. A rough estimate of the occurrence frequency of LOX genes in bacteria suggested that among the bacterial genomes sequenced to date, <0.5 % carry potential LOX genes.…”
Section: Bacterial Lox Genes and Lox-isoformsmentioning
confidence: 99%
“…Lipoxygenases (LOX) are found in a wide variety of organisms throughout the Planta, Animalia, Bacteria and Fungi kingdoms (Gilbert et al, 2011;Hansen et al, 2013;Nemchenko et al, 2006;Oliw, 2002). LOXs are iron-or manganese-containing dioxygenases that catalyze the conversion of unsaturated fatty acids (UFA) into the corresponding hydroperoxides called oxylipins (Mita et al, 2007).…”
Section: Lipoxygenase and Its Biological Rolementioning
confidence: 99%
“…These oxylipins have important signaling functions in many organisms, though the language of oxylipins is not fully understood. Fungal LOXs are involved in an interaction between plants and fungi by using the LOX signaling pathway to infect plant tissue (Hansen et al, 2013;Tsitsigiannis et al, 2005). Oxylipins are also reported to have a role in antimicrobial or defense mechanisms in plants and animals, in animal cell division, and to play a role in plant seed germination (Feussner et al, 2001;Peters-Golden, 1998;Pidgeon et al, 2007;Prost et al, 2005).…”
Section: Lipoxygenase and Its Biological Rolementioning
confidence: 99%
See 1 more Smart Citation